Parenting in the context of driving: Spanish adaptation of the Family Climate for Road Safety (FCRSS) for parents and children - Doncel Pablo (2023)
The Family Climate for Road Safety Scale (FCRSS; Taubman – Ben-Ari & Katz – Ben-Ami, 2013) is a comprehensive measure originally developed in Israel to assess parent-children relations in the specific context of driving. The scale consists of seven dimensions: Modelling, Feedback, Communication, Monitoring, Messages, Limits, and Non-commitment to Safety. While the original FCRSS examines the young drivers’ perception across the seven domains, a version applicable to parents has also been developed by the same authors. The current study investigates the validity and reliability of the FCRSS-Spain for both parents and young drivers. A total of 377 parents (199 fathers and 178 mothers) and 243 of their children (143 daughters and 100 sons) responded tothe FCRSS-Spain versions and provided sociodemographic data. In addition, the young drivers completed the Spanish version of the Multidimensional Driving Style Inventory (MDSI-Spain). Results from exploratory structural equation modelling (ESEM) indicate that six out of the seven FCRSS domains were replicable among Spanish drivers. The Messages dimension did not emerge as a consistent factor in the FCRSS for either parents or young drivers. All six factors demonstrated good internal consistency reliability (ordinal alpha coefficients exceeding 0.70), except for Non-commitment to safety. Significant differences were found between mothers and fathers in various FCRSS dimensions in the predicted direction, whereas no significant differences in FCRSSscores were found between young men and young women. As expected, associations were found between parents’ scores in various FCRSS dimensions and the reckless, angry, dissociative, anxious, and careful driving styles reported by the young drivers, as well as between young drivers’ FCRSS scores and their self-reported reckless, angry, dissociative, anxious, and careful driving styles.